Are unmanned smart hotels du jour or are they here forever? Experiential pathway analysis of antecedents of satisfaction and loyalty. (July 2022) - Chang, Yee-Shan; Cheah, Jun-Hwa; Lim, Xin-Jean; Morrison, Alastair M.; Kennell, James S.
Abstract: Unmanned hotels are regarded as the future of hospitality in a post-Covid 19 world, based upon smart, contactless technologies. The purpose of this research was to determine if unmanned smart hotels create more positive outcomes such as enhanced experiential satisfaction and loyalty. Grounded on Cognitive Appraisal Theory, scholars support the notion that psychological states such as experiential motivation and confidence enhance outcomes. An online survey was conducted with 364 guests of unmanned smart hotels. Structural equation modeling results with partial least squares path analysis indicated that experiential quality, confidence, motivation, and satisfaction were positively associated with loyalty. Several recommendations were provided for the unmanned smart hotel literature and practices with regards to improving the effectiveness of guest experiences. Highlights: This study examines the experiential pathway of the unmanned smart hotel. Cognitive Appraisal Theory was used to explain the proposed relationships. Data were collected using purposive technique and analysed via PLSPM. Results found that loyalty was affected by quality and psychological states. Psychological states and satisfaction sequentially mediated the direct path.